2001
DOI: 10.1590/s0100-40422001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Filmes de metal-hexacianoferrato: uma ferramenta em química analítica

Abstract: Recebido em 26/11/99; aceito em 11/12/00 METAL-HEXACYANOFERRATE FILMS: A TOOL IN ANALYTICAL CHEMISTRY. Chemically modified electrodes based on hexacyanometalate films are presented as a tool in analytical chemistry. Use of amperometric sensors and/or biosensors based on the metal-hexacyanoferrate films is a tendency. This article reviews some applications of these films for analytical determination of both inorganic (e.g. As 3+ , S 2 O 3 2-) and organic (e.g. cysteine, hydrazine, ascorbic acid, gluthatione, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
10

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
27
0
10
Order By: Relevance
“…Thin films of materials such as Prussian blue and related materials can be formed on the electrode surface and show interesting properties. 102,[107][108][109][110] Mattos and Gorton 110 have shown that glucose biosensors can be constructed using Prussian blue films, with excellent performance. An example from Stradiotto and coworkers 101,102 of the use of Prussian blue films as an amperometric sensor to determine persulfate anions in hair bleach "booster" is shown in Figure 2.…”
Section: Chemically Modified Electrodesmentioning
confidence: 99%
“…Thin films of materials such as Prussian blue and related materials can be formed on the electrode surface and show interesting properties. 102,[107][108][109][110] Mattos and Gorton 110 have shown that glucose biosensors can be constructed using Prussian blue films, with excellent performance. An example from Stradiotto and coworkers 101,102 of the use of Prussian blue films as an amperometric sensor to determine persulfate anions in hair bleach "booster" is shown in Figure 2.…”
Section: Chemically Modified Electrodesmentioning
confidence: 99%
“…Nickel hexacyanoferrate ͑NiHCNFe͒, 7 cobalt hexacyanoferrate ͑CoHCNFe͒, 8,9 and copper hexacyanoferrate ͑Cu-HCNFe͒ 10 have been used as mediators in oxidase-based biosensors. 11 However, the sensitivities achieved with these materials during H 2 O 2 detection, even in electrolytes containing K + , are much lower than those measured with a Prussian Blue modified electrode.…”
mentioning
confidence: 94%
“…Besides Prussian Blue, other metal hexacyanoferrate used as mediators in oxidase based biosensors are copper hexacyanoferrate (CuHCNFe) [5][6][7], cobalt hexacyanoferrate (CoHCNFe) [8][9][10][11] and nickel hexacyanoferrates (NiHCNFe) [12][13][14].…”
Section: E-mail Address: Storresi@iquspbr (Si Córdoba De Torresi)mentioning
confidence: 99%